Rostral middle frontal gyrus thickness mediates the relationship between genetic risk and neuroticism trait. (23rd November 2020) - Song, Li; Zhou, Zheyi; Meng, Jie; Zhu, Xingxing; Wang, Kangcheng; Wei, Dongtao; Qiu, Jiang
Abstract: Neuroticism is a robust personality trait associated with multiple mental disorders. Heretofore, research on the relationship among genes, brain, and behavior to explore individual differences in neuroticism is scarce. Hence, in this study ( N = 630), genetic data, self‐reported neuroticism, and brain structural data were combined to explore whether the cortical thickness (CT) of brain regions mediated the relationship between the polygenic risk score (PRS) of neuroticism and NEO neuroticism (NEO‐N), and the enrichment analysis was performed to reveal the underlying mechanism of their relationship. Results showed that the PRSs were significantly associated with NEO‐N scores ( p < .05). The CT of left rostral middle frontal gyrus was negatively related to the best PRS in PRSice (PRSbest ) or the PRS at 0.05 threshold (PRS0.05 ) (corrected p < .05), which was also found to mediate the association between the PRS and NEO‐N (PRSbest : ab = .012, p < .05; PRS0.05 : ab = .012, p < .05). Enrichment analysis revealed that these genes were mainly involved in biological adhesion, cell adhesion, neuron part, and synapse part, which were associated with the abnormal thickness of frontal cortex. By integrating genetic, brain imaging, and behavioral data, our research initially revealed the neurogenetic underpinnings of neuroticism, which is helpful for understanding individual differences in neuroticism. Abstract : Neural characteristics play a key role in the relationship between genetic variants and psychological function. However, this kind of research is scarce in neuroticism. Our study integrated data from genetic variants, neurotic trait, and brain imaging to explore the potential neurogenetic basis of neuroticism, which provides a broader perspective for understanding individual differences in neuroticism.